The Lower Kazanian Substage in the Key Section: Lithologies and Paleoenvironments Based on the ESR Data - E.I. Fakhrutdinov; N.G. Nurgalieva; N.M. Khassanova; V.V. Silantiev (Учёные записки Казанского университета: Серия Естественные науки)
The Lower Kazanian sedimentary succession was considered based on the data from the lithological and stratigraphic description and ESR obtained for the outcrop section within the basin of the Sheshma and Inesh Rivers (Republic of Tatarstan). The Lower Kazanian facial composition correlates with the specific composition and variations of the paramagnetic centers Mn2+, SO3–, SO2–, PO2–, C600, and E'. These ESR labels can be used as facial and chemostratigraphic criteria to stratify and correlate the Lower Kazanian sections in Volga-Kama region.